ETS factors are required but not sufficient for specific patterns of enhancer activity in different endothelial subtypes - Neal, A; Nornes, S; Louphrasitthiphol, P; Sacilotto, N; Preston, MD; Fleisinger, L; Payne, S; De Val, S (Elsevier, 2021)
Correct vascular differentiation requires distinct patterns of gene expression in different subtypes of endothelial cells. Members of the ETS transcription factor family are essential for the transcriptional activation of arterial and angiogenesis-specific gene regulatory elements, leading to the hypothesis that they play lineage-defining roles in arterial and angiogenic differentiation directly downstream of VEGFA signalling. However, an alternative explanation is that ETS binding at enhancers and promoters is a general requirement for activation of many endothelial genes regardless of expression pattern, with subtype-specificity provided by additional factors. Here we use analysis of Ephb4 and Coup-TFII (Nr2f2) vein-specific enhancers to demonstrate that ETS factors are equally essential for vein, arterial and angiogenic-specific enhancer activity patterns. Further, we show that ETS factor binding at these vein-specific enhancers is enriched by VEGFA signalling, similar to that seen at arterial and angiogenic enhancers. However, while arterial and angiogenic enhancers can be activated by VEGFA in vivo, the Ephb4 and Coup-TFII venous enhancers are not, suggesting that the specificity of VEGFA-induced arterial and angiogenic enhancer activity occurs via non-ETS transcription factors. These results support a model in which ETS factors are not the primary regulators of specific patterns of gene expression in different endothelial subtypes.